Proceedings of International Conference on Recent Advancement on Computer and Communication ICRAC 2017 - Tiwari, Basant; Tiwari, Vivek; Das, Kinkar Chandra; Mishra, Durgesh Kumar; Bansal, Jagdish C.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
The book is a compilation of best papers presented at International Conference on Recent Advancement in Computer and Communication (ICRAC 2017) organized by IMPLab Research and Innovation Foundation, Bhopal, India. The book covers all aspects of computers and communication techniques including pervasive computing, distributed computing, cloud computing, sensor and adhoc network, image, text and speech processing, pattern recognition and pattern analysis, digital signal processing, digital electronics, telecommunication technologies, robotics, VLSI technologies, embedded system, satellite communication, digital signal processing, and digital communication. The papers included are original research works of experts from industry, government centers and academic institutions; experienced in engineering, design and research.
Preface -- About the Editors -- Table of Contents -- 70 papers -- Author Index.
Keywords: Signal processing; Control engineering; Robotics; Automation; Computational intelligence; Signal, Speech and Image Processing; Control, Robotics, Automation; Computational Intelligence